Fire Hazard in an Anesthesia Machine: A Case Report. Issue 7 (25th July 2022) - Sokhal, Suman; Sokhal, Navdeep; Sharma, Pradeep; Chouhan, Rajendra Singh
Abstract : An operating room (OR) fire is a rare event but may cause critical harm to patients and health care personnel. We present 2 fire incidents in the rear cabinet of an anesthesia machine, not previously reported in the literature. An anesthesia machine in standby mode is considered safer than in use, but in the first case, the fire occurred while the machine was on standby mode. In another case, the fire erupted while surgery was in progress. Here, we discuss the management of an anesthesia machine fire and emphasize the need for improved fire safety in advanced anesthesia machines.